Exploring the differentiation potential of adipose tissue-derived mesenchymal stromal/stem cells and progenitor buccal epithelial cells into urothelial cells - Buhl, Monika; Jundziłł, Arkadiusz; Dąbrowski, Paweł; Szeliski, Kamil; Rasmus, Marta; Kloskowski, Tomasz; Kaźmierski, Łukasz; Drewa, Tomasz; Pokrywczyńska, Marta (Frontiers in Bioengineering and Biotechnology, 2026)
BackgroundThe intestinal wall is the most commonly used substitution material in reconstructive urology. However, this strategy is associated with many complications. Tissue engineering techniques can replace the intestinal wall with an in vitro-created urinary tract substitute. Biomaterial seeding with urothelial cells (UCs) would increase the success of the regeneration process. The problem in many patients requiring urinary reconstruction is the lack of autologous UCs. This study aimed to compare the differentiation potential of porcine mesenchymal adipose tissue-derived stromal/stem cells (AD-MSCs) and progenitor buccal epithelial cells (pBECs) toward UCs. UCs, AD-MSCs, and BECs were isolated from tissues harvested from domestic pigs. The conditioned medium was collected from UC cultures (UC-CM) between the first and third passage (n = 5). AD-MSC and BEC cultures were exposed to UC-CM for 7 and 14 days, respectively. UCs from the third passage (day 0) were used as a positive control. The differentiation effect of UC-CM was characterized by analysis of selected UC-typical markers at the mRNA and protein levels.ResultsAD-MSCs subjected to urothelial differentiation changed their morphology from fibroblast-like to epithelium-like. In BECs, the differentiation factor increased the expression of urothelial markers, including CK8, UPK1B, and UPKIII.ConclusionThis study demonstrated that pBECs have a higher potential to differentiate toward urothelial-like cells than AD-MSCs. UC-CM is the source of factors inducing the differentiation of pBECs toward urothelial-like cells. Buccal epithelium can be used as a cell source for reconstructive urology applications.